Ideological Aspects of the Activities of Political Parties (Asian countries cases) - Bekzod Najmiddinov (Zien Journals, 2023)
This article analyzes influence of the ideological aspects of the activities of political parties in the political life of leading Asian countries such as China and Japan, and the role of political parties at the social and economic development of this countries
Keywords: ideological aspect; political party; political activity